UNLOCKING TEACHERS’ MOTIVATION: The Influence of Compensation and Work Environment in Boosting Teachers’ Teaching Skills - Sabilil Muttaqin; Nofi Maria K; Diana Sarifah; Syafiuddin Syafiuddin (STAI ALHIKMAH Jakarta, 2023)
AbstractThis study aims to examine the influence of compensation and work environment on teachers’ motivation to improve their teaching skills. The study focuses on three variables: compensation, work environment, and teacher motivation to enhance teaching skills. This research adopts a mixed-methods approach. Data were collected through observations, interviews, and questionnaires. Quantitative data were obtained from 40 teachers at Sultan Hasanuddin Jakarta Foundation. The result of the quantitative analysis indicates that both compensation and work environment do not have a significant effect on teacher motivation to teach and innovate (with a significance value of 0.304). However, observational data and interview results demonstrate that teachers are motivated to innovate when provided with certain compensation and tailored with good and solid work environment. The findings suggest that compensation and work environment can be employed to foster teacher motivation and enhance teaching skills.AbstrakPenelitian ini bertujuan untuk melihat pengaruh kompensasi dan lingkungan kerja terhadap motivasi guru untuk meningkatkan keterampilan mengajar mereka. Penelitian ini berfokus pada tiga variabel: kompensasi, lingkungan kerja, dan motivasi guru untuk meningkatkan keterampilan mengajar. Penelitian ini menggunakan metode campuran. Data dikumpulkan melalui observasi, interview dan kuesioner. Data kuantitatif diperoleh dari 40 orang guru di Yayasan Sultan Hasanuddin Jakarta. Hasil analisis kuantitatif menunjukkan bahwa baik kompensasi maupun lingkungan kerja tidak memiliki pengaruh signifikan terhadap motivasi guru untuk mengajar dan berinovasi (dengan nilai signifikansi sebesar 0,304). Namun, data observasi dan hasil wawancara menunjukkan bahwa guru termotivasi untuk berinovasi ketika diberikan kompensasi tertentu dan didukung dengan lingkungan kerja yang kondusif. Temuan ini menunjukkan bahwa kompensasi dan lingkungan kerja dapat digunakan untuk memupuk motivasi guru dan meningkatkan keterampilan mengajar.